MINIMALLY INVASIVE TREATMENT OF DENTAL EROSIONS IN GASTRO-ESOPHAGEAL REFLUX DISEASE - Andrei Picos; Ioana Chifor; Alina Rotar; Andreea Răchişan; Alina Monica Picos (Amaltea Medical Publishing House, 2018)
Digital planning based on professional oral photographs and films is needed in order to realise minimal invasive treatments of dental erosions (DE) in gastroesophageal reflux disease (GERD). In the first stage a wax-up is made, followed by dental mock-up, in order to adjust functional and aesthetics factors and to guide the dental preparations. Composite, ceramic materials and modern cements offer the possibility of restoring affected functions like aesthetics, fonation and mastication, keeping healthy dental tissue almost intact.